2007
DOI: 10.1139/f07-041
|View full text |Cite
|
Sign up to set email alerts
|

Is boldness towards predators related to growth rate in naïve captive-reared Arctic char (Salvelinus alpinus)?

Abstract: Previous studies have shown that the antipredator responsiveness of fish degenerates through generations in captive breeding. However, detailed knowledge of the underlying mechanism is still largely lacking. We tested the hypothesis that hatchery fish supposedly selected for faster growth in the hatchery environment are bolder towards predators than their slower-growing conspecifics. This was examined by comparing the antipredator behavior of predator- naïve fast- and slow-growing individuals of a captive-bred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
6
3
Order By: Relevance
“…In the literature, both positive and negative associations, or no association at all have been found between growth rate ⁄ developmental time and boldness (e.g. Laakkonen & Hirvonen 2007;Biro & Post 2008;Heg, Schurch & Rothenberger 2011), which suggest that growth rate and boldness are not as tightly coupled as suggested (Adriaenssens & Johnsson 2008). Therefore, the association between boldness and immunity as well is likely highly dependent on the environment and resource availability (Koolhaas 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, both positive and negative associations, or no association at all have been found between growth rate ⁄ developmental time and boldness (e.g. Laakkonen & Hirvonen 2007;Biro & Post 2008;Heg, Schurch & Rothenberger 2011), which suggest that growth rate and boldness are not as tightly coupled as suggested (Adriaenssens & Johnsson 2008). Therefore, the association between boldness and immunity as well is likely highly dependent on the environment and resource availability (Koolhaas 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To fully address concerns about directional selection for specific BTs in domesticated populations, however, more studies are needed that adopt an individual level approach and compare BT distributions between hatchery and wild strains. Recent studies that have collected individual‐level data in hatcheries report wide behavioural variation among individuals, implying a reduced influence of directional selection with respect to behaviour (Laakkonen & Hirvonen, 2007; Conrad & Sih, 2009). These results may be mediated by relaxed rather than directional selection in captive environments, ultimately leading to increased variance in behavioural traits (McPhee, 2004).…”
Section: Implications For Fisheries Managementmentioning
confidence: 99%
“…This was not observed in Takvatn and Fjellfrøsvatn in the same drainage system (Klemetsen et al, 2002a;Amundsen et al, 2008). Experimental studies have shown that burbot may induce antipredator behaviour in Arctic charr and juveniles of this species strongly avoid contact with burbot (Hirvonen et al, 2000;Laakkonen & Hirvonen, 2007). High predation rates may have induced a behavioural habitat shift of Arctic charr away from high risk habitats along the benthic zone.…”
Section: Discussionmentioning
confidence: 84%